Social Benefits of Participation in Scout Tourism (Research Bulletins of the Faculty of Economic Sciences, 2015)
The paper presents the issues of scout tourism. Based on the results of research carried out on 120 person group of scouts, it was presented a broad educational values of scouting, and was noted the social benefits of tourism and the role of scout tourism in filling free time of children and adolescents.
Keywords: tourism; recereation; touring; leisure; scouting